Social Efficacy and Internet Addiction Among University Students: A Descriptive and Correlational Study - Can, Hicret; Onan, Nevin (Addicta: The Turkish Journal on Addictions, 2023)
This descriptive and correlational study was conducted to investigate university student’s social efficacy and internet addiction and the relationship between them. The study was carried out with 380 (142 female, 238 male) university students who are studying at the faculties of Karabük University. The study sample was stratified according to the faculties and formed by a simple random method. Data were collected with Social Efficacy and Social Outcome Expectations Scale and Internet Addiction Scale and evaluated with descriptive statistics and correlation analysis. It was founded that the mean score of the social efficacy subdimension of the Social Efficacy and Social Outcome Expectations Scale was 45.85 (±9.79) and the mean score of the Social Outcome Expectations was 23.23 (±5.37). The mean score for Internet Addiction Scale was 85.82 (±26.99). It was found that Internet Addiction Scale sub-dimension scores were 30.41 (±8.72) for Withdrawal, 24.78 (±8.58) for Controlling Difficulty, 15.89 (±6.58) for Disorder in Functionality, and finally 14.74 (±6.78) for Social Isolation. There was a negative significant correlation between Social Efficacy and Social Outcome Expectations Scale and Internet Addiction Scale total scores and the sub-dimensions (P < .05 for each). In the context of the negative relationship between social efficacy level and internet addiction, it is thought that the attempts to increase students’ social competence can reduce internet addiction.
Keywords: Social efficacy; internet addiction; university students